Asesmen Kenyamanan Taman pada Ruang Terbuka Publik di Kawasan Wisata Tepian Sungai Pangkajene - Syarifah Fatma sari Burhanuddin; Slamet Tri Sutomo; Abdul Mufti Radja (Jurnal Penelitian Enjiniring, 2019)
This research aimed to investigate the ground comfort assessment at the public open space in tourist area of Pangkajene River banks. The research methods used were the qualitative and quantitative method by filling in questionnaires, observation, interviews, and documentation. The samples were chosen using the purposive sampling technique from the users of the park. The data were analyzed using the descriptive analysis, codification, data reduction, matriculation, cross tabulation, and the evaluation system using Likert scale. The research results indicated that the park was inconvenience with the parkconvenience being 61.97%. The effect of the street vendors had caused either positive or negative impacts on the park- the positive impact was that the park had become the largest culinary center in Pangkep town so that it could attract the tourists to visit the park, while the negative impact was that the park looked less beautiful and less hygiene. Keywords: public open space, convenience, park, riverbanks